1973
DOI: 10.1002/chin.197347029
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: INVESTIGATIONS OF COPPER IN AQUEOUS ALKALINE SOLUTIONS BY CYCLIC VOLTAMMETRY

Abstract: Die Kinetik und der Mechanismus der Kathoden‐ und Anodenprozesse an Cu‐ Elektroden in wäßriger KOH‐Lösung werden voltammetrisch untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 1 publication
3
49
0
Order By: Relevance
“…Thus the electrode surface is assumed to be covered with Zn(OH)z layer before the potential scan. Comparing the anodic peaks recorded at potentials > -1.00V for e-brass (in this study) with those reported previously for copper shows that: (a) peak A~ corresponds to the formation of a Cu(OH) film [29][30][31]; (b) peak (or shoulder) A2 is assumed to be due to transformation of Cu(OH) to Cu20 [29]; (c) peak A2 is related to the formation of a Cu(OH)2 or CuO layer [29,30,32]; and (d) peak A 3 (shown only in highly alkaline solutions) is attributable to the oxidation of Cu(II) species to Cu(III) species [33,34].…”
Section: Cyclic Voltammetrymentioning
confidence: 91%
See 1 more Smart Citation
“…Thus the electrode surface is assumed to be covered with Zn(OH)z layer before the potential scan. Comparing the anodic peaks recorded at potentials > -1.00V for e-brass (in this study) with those reported previously for copper shows that: (a) peak A~ corresponds to the formation of a Cu(OH) film [29][30][31]; (b) peak (or shoulder) A2 is assumed to be due to transformation of Cu(OH) to Cu20 [29]; (c) peak A2 is related to the formation of a Cu(OH)2 or CuO layer [29,30,32]; and (d) peak A 3 (shown only in highly alkaline solutions) is attributable to the oxidation of Cu(II) species to Cu(III) species [33,34].…”
Section: Cyclic Voltammetrymentioning
confidence: 91%
“…The cathodic peaks are interpreted as: (a) Peak C1, corresponding to the reduction of Cu(II) species to Cu(I) [29][30][31]; (b) Peak C2, including the reduction of Cu(I) species to Cu(O) [29,[32][33][34][35]; (c) Peak C4, connected with the reduction of Zn(II) species to Zn(O); [27,28] and (d) Peak C3, corresponding to the reduction of Cu(III) species to Cu(II), usually observed for copper [32,35] but which does not appear clearly in the cyclic voltammograms depicted in Figs. 1, 2.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…1) with a potential negative to the peak due to formation of Cu20 (peak 2). Peak 3 is generally associated with formation of Cu(II) species [11,13,19,20]. Peaks 4 and 5 correspond to the Cu(II)/Cu(III) redox couple [11,19].…”
Section: (I) Introductionmentioning
confidence: 99%
“…Ambrose et al [11] reported cyclic voltammograms of copper in 1 mol dm -3 KOH. A voltammogram similar to the one they published is shown in Fig.…”
Section: (I) Introductionmentioning
confidence: 99%
See 1 more Smart Citation